Keputusan untuk Melahirkan dengan Tenaga Kesehatan Terlatih pada Persalinan di Rumah (Analisis Data Survei Demografi dan Kesehatan Indonesia 2017) - Choirunisa, Septyana; Adisasmita, Asri (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: IDHS 2017 reported that there are 20.5% of births occur at home. Among births at home, the presence of a skilled health provider as a birth attendant is critical to ensure safe birth care, especially for mothers who could not access health facilities. However, the presence of skilled birth attendants has not been accessible during home births.Methods: This study used a cross-sectional study design using the 2017 IDHS data. The sample of this study was all women of childbearing age who gave birth at home in 2012-2017. The variables analyzed included maternal education, ownership index, region, place of residence, insurance, pregnancy complications, delivery complications, ANC visits, parity, maternal age at delivery, and delivery assistants. Predictive model analysis was performed using Cox regression.Results: 59.5% of home deliveries were attended by skilled birth attendants, while 40.5% were attended by traditional birth attendants/relatives.  Higher wealth index/socioeconomic status (PR=1.35; 95% CI 1.23-1.48), >4 ANC visits (PR=1.28; 95% 1.18-1.40), and higher education (PR=1.21; 95% CI 1.10-1.32) were the most dominant characteristics affecting the odds of delivery by a skilled birth attendant. Conclusion: Increasing coverage of skilled birth attendants can be pursued by increasing the coverage of recommended ANC visits (>4 times), improving socio-economic status, and increasing maternal education levels.